2019
DOI: 10.1155/2019/3984906
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Alzheimer’s Disease-Like Pathology Progression by Mitochondria-Targeted Antioxidant SkQ1: A Transcriptome Profiling Study

Abstract: Alzheimer’s disease (AD) is the most common type of dementia, with increasing prevalence and no disease-modifying treatment available yet. There is increasing evidence—from interventions targeting mitochondria—that may shed some light on new strategies for the treatment of AD. Previously, using senescence-accelerated OXYS rats that simulate key characteristics of sporadic AD, we have shown that treatment with mitochondria-targeted antioxidant SkQ1 (plastoquinonyl-decyltriphenylphosphonium) from age 12 to 18 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 56 publications
2
35
0
Order By: Relevance
“…Earlier, we have reported that treatment with SkQ1 starting from the predementia phase of AD (consistent with the definition of progressive, amnestic mild cognitive impairment in humans) prevents the neuronal loss and synaptic damage, enhances neurotrophic supply, and decreases Aβ 1-42 peptide levels and tau hyperphosphorylation in the hippocampus of OXYS rats, as well as improving the structural and functional state of mitochondria, thus improving the learning ability and memory [12][13][14][15]. In the present study, by quantifying Aβ in the hippocampus, we confirmed that dietary supplementation with SkQ1 in this age period (from 12 to 18 months) suppresses the progression of AD-like pathology in OXYS rats (Table 1).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Earlier, we have reported that treatment with SkQ1 starting from the predementia phase of AD (consistent with the definition of progressive, amnestic mild cognitive impairment in humans) prevents the neuronal loss and synaptic damage, enhances neurotrophic supply, and decreases Aβ 1-42 peptide levels and tau hyperphosphorylation in the hippocampus of OXYS rats, as well as improving the structural and functional state of mitochondria, thus improving the learning ability and memory [12][13][14][15]. In the present study, by quantifying Aβ in the hippocampus, we confirmed that dietary supplementation with SkQ1 in this age period (from 12 to 18 months) suppresses the progression of AD-like pathology in OXYS rats (Table 1).…”
Section: Discussionsupporting
confidence: 75%
“…The therapeutic effects of supplementation with SkQ1 on the AD-like pathology in OXYS rats are associated with improvement of the mitochondrial apparatus and better neurotrophic supply [11,15]. Accumulating in mitochondria of brain neurons [15], SkQ1 normalizes the expression of genes associated with mitochondria [12]. Ultimately, the reversal of structural and functional damage to mitochondria should decrease the accumulation of neurotoxic aggregates and promote the suppression of p38 MAPKsp activity.…”
Section: Oxys Oxys + Skq1mentioning
confidence: 99%
See 2 more Smart Citations
“…A large body of data also shows mitochondrial dysregulation in AD, with mitochondrial dysfunction mooted as a viable AD treatment target [6], as in many other conditions [7,8]. Targeting mitochondrial function in an AD preclinical model prevents classical AD indicants, viz tangle and plaque formation [9]. Notably, the circadian rhythm drives changes in mitochondrial function and mitochondrial rate-limiting enzymes [10], suggesting that circadian dysregulation impacts core aspects of metabolic function.…”
Section: Introductionmentioning
confidence: 99%